Simile in the Realm of Story (A Study of the Regional Similes in Stories from Five Domains of Story-writing in Iran) - Reza Sadeghi shahpar (مطالعات زبانی و بلاغی)
No doubt the region and environment where artists live in, affect their minds, language and thus, many literary and stylistic techniques that come up in their works. Therefore, while considering regional stories, critics face similarities that are related to local color and regional features. Those similar elements are closely related to the local features of a region and which have had a long -held intimacy with these elements among and taking in those localities. In regional similes, figurative term is an element from the region which is often taken from the local nature or other features of the region in which the story is set. Comparing such similes in regional stories taken from the five regions of story-writing in Iran, namely north, south, Khorasan (east), Kermanshah (west) and Azerbaijan regions, is a worthwhile undertaking which highlights both the stylistic differences and the regional atmosphere affecting their creation. Thus, the present study aims at identifying the differences among the similes used in regional stories and considers such differences as major stylistic features of the stories. It also means to answer this main question whether there are important differences among the similes used in the stories from different regions or the detected differences can be taken as stylistic characteristics distinguishing stories from various regions. As our discussion would indicate, such differences and distinguishing features are quite tangible and regional similes are important elements pointing out the differences among the regional stories.